High-energy dissipative soliton-driven fiber optical parametric oscillator emitting at 1.7 µm. (25th September 2018) - Becheker, R; Tang, M; Hanzard, P-H; Tyazhev, A; Mussot, A; Kudlinski, A; Kellou, A; Oudar, J-L; Godin, T; Hideur, A
Abstract: We report a fiber optical parametric oscillator (FOPO) synchronously pumped in a C-band, delivering high-energy picosecond pulses exceeding the nanojoule level of around 1700 nm. The gain medium is a dispersion-shifted fiber, pumped by highly-chirped pulses from a mode-locked dissipative soliton fiber laser. Optimizing the pump wavelength along with time-dispersion-tuning of the FOPO enabled a broad tunability from 1617–1876 nm for the idler wave. In addition, relative intensity noise levels below −140 dBc Hz −1 have been achieved, paving the way for using such a source in biophotonics and instrumentation.